The Role of the Stakeholders in the Institutionalization of the CSR Reporting In Romania - Raluca Gina Gușe; Alina Almășan; Cristina Circa; Mădălina Dumitru (Journal of Accounting and Management Information Systems (JAMIS), 2016)
Social and environmental aspects are increasingly included in the different types of reports prepared by the Romanian companies. Our research question is which are the forces that drive the institutionalization of the CSR reporting in Romania. We consider the stakeholders as the primary responsible parties for how CSR reporting is implemented. We find that the main initiatives regarding the CSR in Romania belong to the government. Also, the European institutions, through the directives approved, play a major role in CSR reporting in Romania. Our results also show that other stakeholders (companies, the academic environment or Big Four companies) play active roles in the institutionalization of CSR practices and there is an apparent need for more coordinated efforts. Evidence was found with respect to coercive and mimetic isomorphism.
Keywords: M40; 650; CSR; Romania; stakeholders; institutionalization